Peningkatan Proses dan Hasil Belajar Matematika Menggunakan Model Project Based Learning di Kelas III SD - Tri Maryani; Puput Wahyu Hidayat; Refril Dani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study turned into influenced through the low mathematics learning outcomes of third-grade students at SDN 004/II Jaya Setia, in which the majority had no longer but reached the minimum getting to know Mastery standards (KKTP). This trouble changed into suspected to stem from teacher-focused getting to know methods that lacked version and did no longer actively engage students in the mastering manner. The cause of this research became to improve both the mastering process and mathematics success by way of enforcing the undertaking based totally studying (PjBL) model. The observe used a lecture room action research (car) design, performed in cycles, every along with planning, movement, statement, and mirrored image ranges. The research subjects were 20 students, comprising 14 boys and six girls. statistics series techniques included instructor and pupil observation sheets, learning outcome assessments, and documentation. The effects indicated that the software of the PjBL version appreciably better student engagement and participation in studying activities. moreover, the proportion of college students assembly the KKTP improved from fifty five% in the first cycle to eighty five% inside the second cycle. it is able to be concluded that the mission based totally mastering model is powerful in improving each the mastering manner and college students' educational overall performance in mathematics. consequently, it's far endorsed as an progressive opportunity for coaching mathematics at the elementary college level.